Out-of-Court Settlement of Customary Land Rights Disputes of the Malamoi Tribe within the Framework of Land Law Reform - Lestaluhu, Rajab; Kurniati, Nia; ., Gusrizal; Judiasih, Sonny Dewi (Journal of Ecohumanism, 2025)
Indonesia faces the challenge of balancing food security and forest preservation while ensuring its legal system serves as both a foundation and driver of effective governance. This study examines customary dispute resolution within the Malamoi tribe, focusing on the resolution of customary land disputes and its implications for land law reform. The research employs a normative juridical approach, utilizing document studies for data collection and normative qualitative analysis. Findings reveal that the Malamoi tribe maintains customary law as a means of resolving disputes, providing a sense of justice and restoring balance in their community through traditional court processes and sanctions. However, these customary decisions lack formal legal recognition, as Sorong City does not have regulations supporting the application of Malamoi customary law. Despite this, customary land release conditions set by tribal chiefs are acknowledged for land ownership registration. Furthermore, the study proposes judicial recognition of customary resolutions within Indonesia’s legal framework to address conflicts between customary and national court decisions, particularly concerning land disputes crucial for community livelihoods. This approach aligns with efforts to reform land law and harmonize customary and formal legal systems.